Cardiac sympathetic activity in 22q11.2 deletion syndrome. (1st June 2016) - Verschure, Derk O.; Boot, Erik; van Amelsvoort, Thérèse A.; Booij, Jan; van Eck-Smit, Berthe L.F.; Somsen, G. Aernout; Verberne, Hein J.
Abstract: Aim: 22q11.2 deletion syndrome (22q11.2DS) affects catechol- O -methyl-transferase (COMT), which involves the degradation of norepinephrine (NE). Clinically, adults with 22q11.2DS are at increased risk for sudden unexpected death. Although the causes are likely multifactorial, increased cardiac sympathetic activity with subsequent fatal arrhythmia, due to increased levels of NE, should be considered as a possible mechanism predisposing to this premature death. The purpose of this study was to determine whether cardiac sympathetic activity is increased in 22q11.2DS, both at baseline and following an acute NE depletion with alpha-methyl- para -tyrosine (AMPT). Methods: Five adults with 22q11.2DS and five age- and sex-matched healthy controls underwent 2 sessions with either AMPT or placebo administration before 123 I- m IBG scintigraphy. Heart-to-mediastinum ratios (H/M) were determined from the images 15 min (early) and 4 h (late) after administration of 123 I- m IBG and the washout (WO) was calculated as an indicator of adrenergic drive. Results: At baseline there were no significant differences in both early and late H/M between 22q11.2DS and controls. However, there was a significant difference in WO between 22q11.2DS and controls (− 4.92 ± 2.8 and − 10.44 ± 7.2, respectively; p = 0.027), but a "negative WO" does not support an increased sympathetic drive. In addition there was a trend towards a higher late H/M after AMPT administration compared to baseline which was more pronounced in 22q11.2DS. Conclusion: This study for the first time suggests normal cardiac sympathetic activity in adults with 22q11.2DS assessed by 123 I- m IBG scintigraphy. Although there is a small difference in adrenergic drive compared to healthy subjects, this most likely does not explain the increased unexpected death rate in the 22q11.2 DS population.